Mid-IR Intraband Photodetectors with Colloidal Quantum Dots - Xue Zhao (Coatings, 2022)
In this paper, we investigate an intraband mid-infrared photodetector based on HgSe colloidal quantum dots (CQDs). We study the size, absorption spectra, and carrier mobility of HgSe CQDs films. By regulating the time and temperature of the reaction during synthesis, we have achieved the regulation of CQDs size, and the number of electrons doped in conduction band. It is experimentally verified by the field effect transistor measurement that dark current is effectively reduced by a factor of 10 when the 1Se state is doped with two electrons compared with other doping densities. The HgSe CQDs film mobility is also measured as a function of temperature the HgSe CQDs thin film detector, which could be well fitted by Marcus Theory with a maximum of 0.046 ± 0.002 cm2/Vs at room temperature. Finally, we experimentally discuss the device performance such as photocurrent and responsivity. The responsivity reaches a maximum of 0.135 ± 0.012 A/W at liquid nitrogen temperature with a narrow band photocurrent spectrum.